Correlation of Body Weight and Body Length with The Size of Balinese Pig’s Testis That Semi-Traditionally Maintained - I P., Andre J. S.; Sumardani, N. L. G.; Putri, T. I. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
The study aimed to determine the correlation of body weight and body length with the size of Balinese pig testes that semi-traditionally maintained. This research was conducted in Banjar Losan, Takmung Village, Klungkung District, Klungkung Regency for 4 months. Nutritional analysis of Balinese pig feed was carried out in the Laboratory of the Faculty of Agricultural Technology, Udayana University, Denpasar. Research used 4 male pigs (not castrated) aged (3 months) with initial weight: pig I (5 kg), pig II (5kg), pig III (3.5 kg), and pig IV (3.5 kg). The study was conducted by analyzing the correlation coefficient, ie each pig measured body weight (X1), body length (X2), testicular length (Y1), and testicular width (Y2). The observed variables included body weight, body length, testicular length, and width testes. The results showed that there was a strong and statistically significant relationship between the correlation of body weight and body length with testicular size in male Balinese pigs. Based on the results of the study it can be concluded that body weight and body length are positively and significantly correlated to the size of Balinese pig testes that are maintained in traditional cultures. Keywords: balinese pigs, correlation, weight, testis